Microstructure and phase composition of ZrN/SiNx multilayered coatings formed by reactive magnetron deposition - Uglov, Vladimir V.; Zlotski, Sergey V.; Solodukhin, Igor A.; Malashevich, Alexander A. (Journal of the Belarusian State University. Physics, 2019)
In the present work, the microstructure and phase composition of multilayered nanoscaled ZrN/SiNx coatings with different thicknesses of individual ZrN and SiNx layers were investigated. The results of transmission electron microscopy (HRTEM) showed that multilayer ZrN/SiNx coatings formed by reactive magnetron deposition are alternating layers of ZrN and SiNx. The Xray reflectometry (XRR) method made it possible to determine the density, thickness, and surface roughness of individual ZrN and SiNx layers. Xray diffraction analysis showed that ZrN and SiNx layers have a crystalline and amorphous structure, respectively. The phase composition of mononitride ZrN coatings is characterized by the presence ZrN phase with preferential orientation (111). Phase composition results indicate a change in the preferential orientation from (111) observed for the mononitride ZrN films, to (200) forming in the multilayered ZrN/SiNx coatings.